(untitled) (REC 2026 - 11th International Workshop on Reliable Engineering Computing: Reliability Computations in a Data and Model-Driven World, 2026)
With the growing demand for refined structural reliability assessments, the influence of higher-order moments on failure probability has garnered increasing attention. However, existing third-order sensitivity methods (SAMoM) cannot reveal the sensitivity of failure probability to fourth-order moments. This paper proposes a fourth-order moment sensitivity analysis method that computes the partial derivatives of failure probability with respect to the mean, standard deviation, skewness, and kurtosis of input variables. Numerical example show that the method maintains the accuracy of SAMoM while, for the first time, reliably estimating the sensitivity of failure probability to kurtosis.